Personalised gravitational loading of the cervical spine from biplanar X-rays for asymptomatic and clinical subjects in neutral standing position. (February 2022) - Muth-seng, Christophe; Huneidi, Maxime; Heidsieck, Cécile; Laporte, Sébastien; Le Coz, Jean-Yves; Gille, Olivier; Skalli, Wafa
Abstract: Background: As a leading cause of disability with a high societal and economic cost, it is crucial to better understand risk factors of neck pain and surgical complications. Getting subject-specific external loading is essential for quantifying muscle forces and joint loads but it requires exertion trials and load cells which are uncommon in clinical settings. Methods: This paper presents a method to compute the gravitational loading at four levels of the cervical spine (C3C4, C4C5, C5C6, C6C7) in neutral standing position from biplanar radiographs exclusively. The resulting load was decomposed in local disc frames and its components were used to compare different populations: 118 asymptomatic subjects and 46 patients before and after surgery (anterior cervical discectomy and fusion or total disc replacement). Comparisons were performed at C6C7 and the upper level adjacent to surgery. Findings: Significant changes in gravitational loading were observed with age in healthy subjects as well as in patients after surgery and have been associated with changes in posture. Interpretation: This approach quantifies the influence of postural changes on gravitational loading on the cervical spine. It represents a simple way to obtain necessary input for muscle force quantification models in clinical routine and to use them for patient evaluation. The study of the subsequent subject-specific spinal loading could help further the understanding of cervical spine biomechanics, degeneration mechanisms and complications following surgery. Highlights: Method to obtain gravitational cervical spine loading from biplanar X-rays. Significant differences in loading with age and cervical surgery. Differences related to postural changes. Should facilitate muscle force quantification for patient evaluation.